2016
DOI: 10.1128/jvi.01178-16
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Requirement of Murine Leukemia Virus p12

Abstract: The p12 protein of murine leukemia virus (MLV) Gag is associated with the preintegration complex (PIC), and mutants of p12 (PM14) exhibit defects in nuclear entry/retention. Mutants of the phosphorylated serine 61 also have been reported to have defects in the early life cycle. Here we show that a phosphorylated peptide motif derived from human papillomavirus 8 (HPV-8), the E2 hinge region including residues 240 to 255, can functionally replace the main phosphorylated motif of MLV p12 and can rescue the viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…5C). Tethering is also observed using the corresponding p12-M63-GFP minimal tethering domain (p12 61-71 -M63-GFP) (31). These results (i) show that the p12 C-terminal motif, from S61 through R71, is necessary and sufficient for the chromatin binding function of MLV p12 and (ii) uncovered that an N-terminal region is involved in suppressing this chromatin binding.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…5C). Tethering is also observed using the corresponding p12-M63-GFP minimal tethering domain (p12 61-71 -M63-GFP) (31). These results (i) show that the p12 C-terminal motif, from S61 through R71, is necessary and sufficient for the chromatin binding function of MLV p12 and (ii) uncovered that an N-terminal region is involved in suppressing this chromatin binding.…”
Section: Resultsmentioning
confidence: 50%
“…Details shown in Fig. 6 relating to the regulation of late viral functions and the role of phosphorylation are expanded in an accompanying article (31). The model is based on structural studies of the Rous sarcoma virus (RSV) Gag (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the NSD3 ET binding motif is flanked by lowcomplexity regions [DisMeta, (Huang et al, 2014)], including a Pro-rich sequence N-terminal to the ETBM (Supplementary Figure S4), that are predicted to be intrinsically-disordered. Recently it was proposed that BET proteins interact with MLV IN after p12-mediated nuclear retention of the viral PIC (Brzezinski et al, 2016a, Brzezinski et al, 2016b, Borrenberghs et al, 2019. Using FRET-based studies, the interaction of BET proteins with MLV IN was shown to cause alteration in the quaternary structure of IN within the PIC (Borrenberghs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether p12 directly binds chromatin or if it interacts with another chromatin binding factor. Notably, fluorescence microscopy revealed that recombinant Mo-MLV p12 did not localise to mitotic chromatin in mammalian cells [ 19 ]. One possibility is that another viral protein is required for chromatin tethering.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the inability of recombinant Mo-MLV p12 to bind chromatin could be due to the absence of an essential post-translational modification. Previous studies have identified p12 as the main phosphorylated protein in Mo-MLV with the majority of phosphorylation occurring on serine-61 within the CTD [ 19 , 23 25 ]. In contrast with viral p12, recombinant Mo-MLV p12 was found to be non-phosphorylated in mammalian cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%